Riverbank filtration as a conjunctive use between surfacewater and groundwater for water security - Shamsuddin, Mohd Khairul Nizar (2019)
Climate change has caused limited water resources in many parts of the world. In fact, high occurrences of river pollution in Malaysia have led to the decrease in drinking water resources. This causes the closure of water intakes and water treatment plants which have impacted water supply, and thus, affected economic activities in the manufacturing industry and other sectors. Riverbank filtration (RBF) is one of the solutions to providing raw water for public supply in tropical countries. RBF is natural process using natural soil (aquifer) to treat surface water and seeping from the bank or bed of a river or lake to the pumping wells where, surface water and groundwater were used conjunctively for water supply. In this study, a pilot site consisting of three areas located at Langat river basin, Linggi river basin and Muda river basin based on hydrogeology and land use were monitored. Nevertheless, RBF needed to be assessed on its feasibility based on the local site geological characteristics. Therefore, this research was carried out to fill in the knowledge gap in evaluating the capability of combined use groundwater and surface water using RBF system by using a number of research methods. For that reason, measuring the efficiency of RBF involved geophysical data, sieve (particle size) analysis, pumping test data, isotope analysis, statistical tools, numerical modelling, and water quality data technique. The physicochemical and microbiological parameters of the local surface water and groundwater were analysed before and during water abstraction. Abstraction of water revealed a 5– 98 % decrease in turbidity, as well as reductions in HCO3 −, Cl−, SO4 2−, NO3 −, Ca2+, Al3+ and As concentrations compared with those of surface water. In addition, amounts of E. coli, total coliform and Giardia were significantly reduced (99.9 %). However, water samples from test wells during pumping showed high concentrations of Fe2+ and Mn2+. From the numerical modelling, the proposed method performs filtration safely and achieves the ideal pumping rate. Results indicate that the migration of river water into the aquifer is generally slow and depends on the pumping rate and distance from well to the river. Most river water arrives at the well by the end of a pumping period of 1 to 5 days. During the 9.7- day pumping period, 33 % of the water pumped from the well was river water based on the distance at 36 m from river, and 38 % of the water pumped from 18 m distance form river throughout 4.6 day was river water. In examining the interaction between the surface water and the groundwater, environmental isotopes like δ2H and δ18O were studied primarily. The environmental isotope and hydro-chemical sampling results had emphasised that the area near river basin had a connection with the river and groundwater was actively recharging the nearriver shallow alluvial aquifer, via RBF method. The approximate hydraulic conductivity (K) values of samples taken from riverbanks and streambeds, respectively, were then calculated by employing empirical equation methods, pumping test and permeability tests indicated that the value of K was important in clogging processes and the velocities and residence times in the subsoil. Furthermore, samples of groundwater and surface water of standard drinking water quality for both wet and dry seasons have been collected and analysed for various parameters and water indices. Result was indicated that all groundwater and surface water samples can be categorised as excellent and good categories respectively. In conclusion, Malaysia riverbank were suitability of RBF systems had a higher potential area and were able to generate potable drinking water but various method such as geophysical, hydro-chemical, geochemical, stable isotope approaches pumping test, statistical tools and numerical modelling must be priority to applied during the RBF studies. RBF is acceptable as a conjunctive use of surface water and groundwater for national water security applicable during climate change.